Group approach to geometric quantization of two physical groups - Paul Bracken (APL Quantum)
Physical systems as a rule are associated with a symmetry group. One way of quantizing the system is to use this symmetry group to construct a geometric form of quantization procedure. This group quantization procedure is discussed and illustrated here on two different systems. Group cohomology and extensions of groups play a key role. Many important groups in physics can be extended by the local U(1) group. The process is introduced here and applied to two nontrivial systems.